2008
DOI: 10.3174/ajnr.a1105
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Diffusion-Weighted Imaging Protocol for Lesion Detection in Transient Global Amnesia

Abstract: BACKGROUND AND PURPOSE: Diffusion-weighted imaging (DWI) can depict small punctate hyperintense lesions in the hippocampus in transient global amnesia (TGA). The purpose of this study was to find an optimal DWI protocol for lesion detection in TGA by investigating various imaging parameters and imaging timing after symptom onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
80
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 24 publications
(33 reference statements)
3
80
1
3
Order By: Relevance
“…1,2,14 We hypothesize that disruption of the corticohippocampal circuitry without direct involvement of the mesiotemporal region may have caused a clinical syndrome indistinguishable from classic TGA. In both SPECT and PET studies, perfusion abnormalities in the basal ganglia have been reported for TGA but were associated with concomitant medial temporal lobe hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,14 We hypothesize that disruption of the corticohippocampal circuitry without direct involvement of the mesiotemporal region may have caused a clinical syndrome indistinguishable from classic TGA. In both SPECT and PET studies, perfusion abnormalities in the basal ganglia have been reported for TGA but were associated with concomitant medial temporal lobe hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies reported relatively lower incidence of multiplicity, ranging from 5% to 38%. 7,10,22,23 This may be due to increased detectability of high-resolution DWI for smaller lesions, which were missed on lower resolution by partial volume averaging effects. 7,9,22 Therefore, we think that high-resolution DWI with less partial volume averaging might improve lesion contrast in our study.…”
Section: Discussionmentioning
confidence: 99%
“…High b-value (ie, 2000 -3000 seconds/mm 2 ), thin section thickness (ie, 3 mm), and imaging 48 -72 hours after the onset of symptoms increased lesion detectability of DWI. 7,10,18 However, until now, there has been no well-designed study to evaluate the influence of the resolution of DWI on lesion detectability in TGA. In this study, we investigated whether punctuate TGA lesions can be detected more often by increasing the resolution of DWI.…”
mentioning
confidence: 99%
See 2 more Smart Citations